Pengembangan Media Crossword Puzzle Berbasis Problem-Based Learning untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Oktavianingrum, Berliana Aurora; Isdaryanti, Barokah (Paedagogie, 2026)
This study aims to develop a Crossword Puzzle learning media based on Problem-Based Learning (PBL) integrated with the Family 100 game and to test its feasibility and effectiveness in improving the learning outcomes of fifth-grade students of SD Negeri Tugurejo 02, Semarang City. The method used is Research and Development (R&D) with the Borg & Gall model simplified into eight stages. The research subjects were 27 students. Data were collected through tests (pre-test and post-test) and non-tests in the form of observation, interviews, documentation, and questionnaires. Data analysis was carried out using the Shapiro–Wilk normality test, paired t-test, and n-gain test. The results showed that the developed media was categorized as very feasible based on the assessment of material experts (92.5%) and media experts (87%), and received very adequate responses from teachers (96.42%) and students (94%). The effectiveness of the media was seen from the increase in learning outcomes with an n-gain value of 0.8585 on a small scale and 0.7944 on a large scale which is included in the high category. Thus, the Crossword Puzzle learning media based on Problem-Based Learning (PBL) which is integrated with the Family 100 game on the material of Cultural Heritage, My Regional Wealth is suitable and effective for use to improve students' science learning outcomes.